Diagnostic accuracy of frozen section: experience at Fatima Jinnah Medical University, Lahore (Journal of Fatima Jinnah Medical University, 2019)
Background: The surgical approach and management depends on frozen section examination results and isvariable for different frozen section results. Frozen section examination is a quick and reliable preliminarydiagnostic intraoperative technique that allows surgeons to take immediate correct decisions at the operatingtable. In this study, the diagnostic accuracy of frozen section examination was determined at Fatima JinnahMedical University, Lahore.Patients and methods: Frozen section database from 1st January 2016 to 31st December 2017 wasretrospectively reviewed and compared with permanent sections to determine the diagnostic accuracy,sensitivity and specificity of frozen section technique. The study included 103 cases. The cases were dividedinto concordant and discordant cases. The diagnostic disagreements were analyzed to determine the cause ofdiscrepancy.Results: Total 103 frozen section specimens were evaluated. The anatomical site was primarily the ovary,axillary lymph node, breast, skin, thyroid, uterus and kidney. Among them 102 (99.03%) cases were concordantand 1 (0.97%) case was discordant. The discordant case was false negative and the specific site was the ovary.There was no false positive result. The overall sensitivity, specificity, diagnostic accuracy, positive predictivevalue and negative predictive value of frozen section examination compared to permanent section were 97.6%,100%, 99%, 100% and 98.4% respectively. For individual anatomic locations, the diagnostic accuracy rangedfrom 97.9% to 100%. The diagnostic discrepancy was due to sampling error.Conclusion: Frozen section is a highly accurate, valuable and reliable technique for making rapid preliminaryintraoperative diagnosis, thus enabling surgeons in taking correct immediate decisions regarding appropriatesurgical approach and further management at the operating table
Keywords: Frozen section; permanent section; accuracy